From Service Delivery to Social Transformation: Repositioning Community Engagement Practices - Oktaviani, Yeni; Xiang, Yang; Wei, Sun (Journal Ligundi of Community Service, 2025)
Community engagement has traditionally been viewed as a means of service delivery, focused on addressing immediate needs such as healthcare, infrastructure, and education. However, there is growing recognition that this approach does not address the deeper structural issues affecting marginalized communities. This study explores the repositioning of community engagement from a service delivery model to one that fosters social transformation. The primary aim is to examine how community engagement can be redefined to empower communities, promote social justice, and drive systemic change. A mixed-methods approach, combining qualitative interviews, focus groups, and surveys, was employed to analyze community engagement practices across three diverse urban and rural settings. Findings indicate that initiatives focusing on social transformation, including participatory decision-making and community-driven projects, led to greater empowerment, improved social cohesion, and more sustainable long-term outcomes. In contrast, service-oriented engagement was associated with short-term solutions and limited community ownership. The study concludes that community engagement should prioritize social transformation, with a focus on addressing root causes of inequality and fostering collective action. Policy recommendations include integrating participatory practices into community development strategies and enhancing community capacity for self-advocacy.